Contralateral S1 function is involved in electroacupuncture treatment-mediated recovery after focal unilateral M1 infarction - Lu-Lu Yao (Wolters Kluwer Medknow Publications, 2022)
Acupuncture at acupoints Baihui (GV20) and Dazhui (GV14) has been shown to promote functional recovery after stroke. However, the contribution of the contralateral primary sensory cortex (S1) to recovery remains unclear. In this study, unilateral local ischemic infarction of the primary motor cortex (M1) was induced by photothrombosis in a mouse model. Electroacupuncture (EA) was subsequently performed at acupoints GV20 and GV14 and neuronal activity and functional connectivity of contralateral S1 and M1 were detected using in vivo and in vitro electrophysiological recording techniques. Our results showed that blood perfusion and neuronal interaction between contralateral M1 and S1 is impaired after unilateral M1 infarction. Intrinsic neuronal excitability and activity were also disturbed, which was rescued by EA. Furthermore, the effectiveness of EA treatment was inhibited after virus-mediated neuronal ablation of the contralateral S1. We conclude that neuronal activity of the contralateral S1 is important for EA-mediated recovery after focal M1 infarction. Our study provides insight into how the S1–M1 circuit might be involved in the mechanism of EA treatment of unilateral cerebral infarction. The animal experiments were approved by the Committee for Care and Use of Research Animals of Guangzhou University of Chinese Medicine (approval No. 20200407009) April 7, 2020.